191k views
0 votes
NEED HELP ASAP

I need answers please ​

NEED HELP ASAP I need answers please ​-example-1

2 Answers

4 votes
Should’ve listened in class buddy
User Alben
by
5.2k points
6 votes

Answer:

Explanation:

10) Cos (x-y) = cos x cos y + sin x sin y

cos 4x cox 3x + sin 4x sin 3x = Cos (4x - 3x)

= cos x

11) = 2*(1² + 2) + 2*(2² + 2²)

= 2*3 + 2*(4+4)

= 6 + 2*8

= 6 + 16

= 22

12) (3) 4x² - 3x - 8 = 0

Reason:

Sum of roots = - Coefficient of x/coefficient of x² = -(-3)/4 = 3/4

Product of roots = constant / coefficient of x² = -8/4 = -2

User Keymap
by
4.5k points